Células dendríticas. Su rol en la terapéutica del cáncer - López Lincuez, María Emilia; Lastiri, José; Argibay, Pablo; Di Rissio, Catalina; Specterman, Sergio; Puricelli, Lidia; Pallotta, Guadalupe (Revista del Hospital Italiano de Buenos Aires, 2004)
.